CD200-CD200R Interaction: An Important Regulator After Stroke - Zhao, Xu; Li, Jing; Sun, Haitao (Frontiers in Neuroscience, 2019)
The high mortality and morbidity rate of stroke is a chronic problem that plagues human society. The activation of microglia is one of the principal reasons why neuroinflammation induces cerebral dysfunction. Because of their vital functions in the regulation of neuroinflammation, microglia constitute an important target for stroke. Given that there is an innate self-preservation mechanism between neurons and microglia, the transmembrane glycoproteins on the surface of their membranes, namely CD200 and CD200R, have become a popular topic of research. Numerous studies have demonstrated that CD200-CD200R interaction, microglial activation, and poststroke neuroinflammatory damage are inextricably linked. In this review, we describe the above relationship from a new perspective. We specifically focus on neuroinflammation after stroke. The role of crosstalk of CD200-CD200R inhibitory immune ligand receptors in immune regulation will also be illustrated. Thus, we will see how poststroke injury can be influenced by the CD200-CD200R crosstalk. Finally, we will discuss the possibility of clinical application of the result of CD200-CD200R interaction to manage neuroinflammatory injury after stroke.